Diskriminantas: Skirtumas tarp puslapio versijų

96 pridėti baitai ,  prieš 9 metus
:Kai <math>x_2=x_3=\left(-\frac{x_1}{2}\right),</math> tai
:<math>x_1^2+x_2^2+x_3^2=x_1^2+\left(-\frac{x_1}{2}\right)^2+\left(-\frac{x_1}{2}\right)^2=x_1^2+\frac{x_1^2}{2}=-2p;</math>
:<math>x_1 x_2+x_1 x_3+x_2 x_3=x_1\cdot\left(-\frac{x_1}{2}\right)+x_1\cdot \left(-\frac{x_1}{2}\right)+\left(-\frac{x_1}{2}\right)\cdot \left(-\frac{x_1}{2}\right)=-x_1^2+\frac{x_1^2}{4}=p.;</math>
:<math>-2(-x_1^2+\frac{x_1^2}{4})=2x_1^2-\frac{x_1^2}{2}=-2p.</math>
 
 
*'''Pavyzdis'''. Išspręsti lygtį
Anoniminis naudotojas